2016
DOI: 10.1016/j.aop.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Non-singular Brans–Dicke collapse in deformed phase space

Abstract: We study the collapse process of a homogeneous perfect fluid (in FLRW background) with a barotropic equation of state in Brans-Dicke (BD) theory in the presence of phase space deformation effects. Such a deformation is introduced as a particular type of non-commutativity between phase space coordinates. For the commutative case, it has been shown in the literature [M A Scheel, S L Shapiro & S A Teukolsky, Phys Rev D 51 4236 (1995)], that the dust collapse in BD theory leads to the formation of a spacetime sing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 161 publications
(105 reference statements)
0
16
0
Order By: Relevance
“…For θ 0, solving the complicated differential equation (23) analytically is impossible. However, it is feasible to derive the general conditions under which the universe can accelerate.…”
Section: Kinetic Inflation and The Horizon Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…For θ 0, solving the complicated differential equation (23) analytically is impossible. However, it is feasible to derive the general conditions under which the universe can accelerate.…”
Section: Kinetic Inflation and The Horizon Problemmentioning
confidence: 99%
“…From ( 28), we observe that the acceleration/deceleration condition of the scale factor completely depends on the evolution of the scalar field, which, in turn, is obtained from a nonlinear differential equation (23). Note that to obtain ä a for the commutative case, θ must be set equal to zero in both ( 23) and (28).…”
Section: Kinetic Inflation and The Horizon Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we have introduced a NC BD setting. Such a scenario bears much resemblance to the settings assumed in NC quantum cosmology or a few classical noncommutative gravitational/cosmological investigations in theories alternative to general relativity [12][13][14][15]).…”
Section: Discussionmentioning
confidence: 86%
“…It has been demonstrated that the singularity can be removed by including quantum effects [29, 28]. coarse grained effects at late times of the evolution of the universe. Recently, various NC cosmological/gravitational frameworks have been constructed to investigate different shortcomings associated to the corresponding standard models [35,40,36,39,38,37]. For instance, in [24], two of us have shown that such source can be borrowed from the NC portions accompanying the standard BD setting.…”
Section: Introductionmentioning
confidence: 99%